EXPLORING THE ETHICAL IMPLICATIONS OF ARTIFICIAL INTELLIGENCE IN DIGITAL MEDIA AND CONTENT GENERATION (Лучшие интеллектуальные исследования, 2025)
Abstract. This article analyzes the role of artificial intelligence (AI) technologies in the field of digital media and content creation and their ethical aspects. Although the processes of content creation using AI are significantly automated, complex ethical issues arise, such as responsibility, transparency, the spread of misinformation, copyright and respect for human values. The article examines the social impact of these issues, regulatory mechanisms and prospects in the conditions of Uzbekistan. It also highlights the importance of international experience and national measures in the field of AI ethics. The article puts forward principles and solutions necessary for the fair and reliable use of AI in the field of digital media.